The Effect Of Adding Latex And Hair Fiber On Concrete - Hendrik (IHSA Institute, 2021)
Along with the development of the construction world, the need for concrete is increasing and the scale of development shows that there will also be more and more concrete needs in the future, thus affecting the development of concrete technology which will demand new innovations regarding the concrete itself. In the construction of high-rise buildings required concrete with high compressive strength. However, to get good quality concrete, high costs are also required. So in this study, an economical additional material will be used which will be added to the concrete in the form of latex and hair fiber. Testing of materials and test objects is carried out in accordance with the applicable Indonesian National Standard (SNI). The latex used is liquid latex. First, the hair fiber is washed in order to clean the dirt and debris attached and then dried in the sun for 2 days, then cut to a size of ± 30 mm. By adding latex with variations of 0.25%, 0.5% and 0.75% it is expected to achieve a concrete quality of 20 MPa and by adding 2% hair fiber and latex with variations of 0.25%, 0.5% and 0.75% is expected to achieve a concrete quality of 20 MPa. The research object used a cylinder with a diameter of 15 cm and a height of 30 cm with the addition of 48 pieces of latex which were tested at the age of 28 days, cylinder with a diameter of 15 cm and a height of 30 cm with the addition of latex and hair fiber as many as 18 pieces were tested at the age of 7 days, and a beam without reinforcement with a length of 60 cm, width 15 cm and height of 15 cm with the addition of latex and hair fiber as much as 3 pieces The Water Cement Factor (FAS) in this study was locked at 0.5. This study was intended to obtain the value of compressive strength, split tensile strength, concrete absorption, slump value in cylinders and flexural strength values ​​in unreinforced beams. From the test results, it was found that the slump value decreased due to the addition of the latex additive and increased due to the addition of the latex and hair fiber additives and then increased along with the increase in the additional variation. The absorption of concrete also decreased with the addition of the latex additive and increased with the addition of the latex additive and hair fiber. The most optimum compressive strength results were obtained in concrete with the addition of 0.75% latex variation, an increase of 13.226% from normal concrete while the most optimum compressive strength results were obtained in concrete with the addition of 0.75% latex variation and 2% hair fiber reduced by 0.94% from normal concrete.